KRÄFTE (MOMENT)-RÜCKKOPPELUNGSSYSTEM VON MECHATRONISCHEN ELEMENTEN - Petrik, O. (Periodica Polytechnica Mechanical Engineering, 1987)
One of the most important part of the operative mechatronical e;ements is the force-(or torque-) feedback unit. The paper gives a surway about the structure of the elastic deformation based sensing system with the connected electronical. unit.